P-262 A PDE4 Inhibitor-antibody Conjugate for Treating Ulcerative Colitis. (February 2017) - Yu, Shan; Pearson, Aaron; Lim, Reyna; Rodgers, David; Li, Sijia; Parker, Holly; Weglarz, Meredith; Hampton, Eric; Bollong, Michael; Shen, Jiayin; Zumbaldo, Claudio; Wang, Danling; et al.
Abstract : Background: Although current treatment strategies for ulcerative colitis have been fairly effective, many ulcerative colitis patients do not respond to such treatments and require a colectomy. Development of new therapeutics is indeed necessary to fulfill unmet medical needs. PDE4 (phosphodiesterase 4) inhibitors, including apremilast and roflumilast, have been demonstrated to be useful in treatment of ulcerative colitis in the pre-clinical animal models, and apremilast is under evaluation in clinical trials for treating ulcerative colitis. However, dose-limiting side effects on the central nervous system (CNS) and gastrointestinal tract (GI), including nausea, emesis, headache, and diarrhea, might impede the establishment of an appropriate therapeutic index for the treatment of ulcerative colitis in a safe and efficacious manner. Given the anti-inflammatory effect of PDE4 inhibitors relies on the suppression of inflammation in various immune cells, all of which express CD11a, we have now developed a targeted therapeutic antibody drug conjugate (ADC), consisting of αCD11a antibody and an analog of a highly potent PDE4 inhibitor GSK256066, to specifically deliver this small molecule into immune cells sparing the neuronal cells of the CNS and GI. This targeted delivery method could be a potential therapeutic strategy for treating ulcerative colitis. Methods: We generated both human and mouse αCD11a-PDE4 inhibitor ADC, consisting of human αCD11a antibody (Efalizumab) or mouse αCD11a antibody (M17), and an analog of a highly potent PDE4 inhibitor GSK256066. The effect of the ADC in inhibiting inflammation was assessed both in primary human and mouse immune cells in vitro, and in a carrageenan-induced air pouch inflammation mouse model in vivo. Results: We show herein human and mouse αCD11a-PDE4 inhibitor ADC suppressed LPS-induced TNFα secretion in human primary monocytes and mouse primary peritoneal cells, respectively. This inhibition of TNFα secretion by mouse αCD11a-PDE4 inhibitor ADC in mouse peritoneal cells was mediated through CD11a, as treatment with excess αCD11a antibody abrogates the ADC's effect and this ADC did not reduce TNFα secretion in MEF cells that were negative for CD11a. In a carrageenan-induced air pouch inflammation mouse model, treatment with the ADC significantly reduced inflammatory cytokine production in the air pouch exudate. In addition, mouse αCD11a-PDE4 inhibitor ADC bound to the lamina propria mononuclear cells and reduced TNFα and IFNγ production in these cells isolated from DSS-induced colitis mouse colons. Conclusions: These results provide evidence for the feasibility of specifically-delivering immune suppressants to immune compartment and the development of PDE4 inhibitor ADC as a promising therapeutic for treating ulcerative colitis.